TUT‐DIS3L2 is a mammalian surveillance pathway for aberrant structured non‐coding RNAs. (19th September 2016) - Ustianenko, Dmytro; Pasulka, Josef; Feketova, Zuzana; Bednarik, Lukas; Zigackova, Dagmar; Fortova, Andrea; Zavolan, Mihaela; Vanacova, Stepanka
Abstract: Uridylation of various cellular RNA species at the 3′ end has been generally linked to RNA degradation. In mammals, uridylated pre‐let‐7 miRNAs and mRNAs are targeted by the 3′ to 5′ exoribonuclease DIS3L2. Mutations in DIS3L2 have been associated with Perlman syndrome and with Wilms tumor susceptibility. Using in vivo cross‐linking and immunoprecipitation (CLIP) method, we discovered the DIS3L2‐dependent cytoplasmic uridylome of human cells. We found a broad spectrum of uridylated RNAs including rRNAs, snRNAs, snoRNAs, tRNAs, vault, 7SL, Y RNAs, mRNAs, lncRNAs, and transcripts from pseudogenes. The unifying features of most of these identified RNAs are aberrant processing and the presence of stable secondary structures. Most importantly, we demonstrate that uridylation mediates DIS3L2 degradation of short RNA polymerase II‐derived RNAs. Our findings establish the role of DIS3L2 and oligouridylation as the cytoplasmic quality control for highly structured ncRNAs. Synopsis: Aberrant RNAs originating from all three nuclear RNA polymerases are targeted by a TUT/DIS3L2 surveillance system, implicating Perlman syndrome exoribonuclease DIS3L2 as a key player in uridylation‐mediated cytoplasmic RNA decay. TUT‐DIS3L2 surveillance (TDS) targets structured aberrant RNA transcripts from all three nuclear RNA polymerases. TDS removes a variety of incorrectly processed ncRNAs, such as snRNAs, tRNAs, Y RNAs, snoRNAs, and transcripts from pseudogenes. Prematurely terminated RNA polymerase II mRNA transcripts (transcription start site associated sequences) escape nuclear degradation and are targeted by TDS in the cytoplasm. Abstract : Aberrant RNAs originating from all three nuclear RNA polymerases are targeted by a TUT/DIS3L2 surveillance system, implicating Perlman syndrome exoribonuclease DIS3L2 as a key player in uridylation‐mediated cytoplasmic RNA decay.